2006
DOI: 10.1002/hep.21070
|View full text |Cite
|
Sign up to set email alerts
|

Localization of oxidized phosphatidylcholine in nonalcoholic fatty liver disease: Impact on disease progression

Abstract: Nonalcoholic steatohepatitis/nonalcoholic fatty liver disease is considered to be a hepatic manifestation of various metabolic disorders. However, its precise pathogenic mechanism is obscure. Oxidative stress and consequent lipid peroxidation seem to play a pivotal role in disease progression. In this study, we analyzed the localization of oxidized phosphatidylcholine (oxPC), a lipid peroxide that serves as a ligand for scavenger receptors, in livers of patients with this steatotic disorder. Specimens of nonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(101 citation statements)
references
References 47 publications
(69 reference statements)
3
94
0
2
Order By: Relevance
“…ERK-, MEK-, and mitogenactivated protein kinase-related pathways are regulated and regulate Jun N-terminal kinase (JNK) expression, which has a pivotal role in obesity and insulin resistance [52]. Phosphatidylcholine, another component of the RA preparation, protects against oxidative stressmediated liver damage [53,54]. It is unlikely that the treatment effects are related to the vitamin E component, which is much lower (60 IU/ day) than doses with documented efficacy [4].…”
Section: Discussionmentioning
confidence: 99%
“…ERK-, MEK-, and mitogenactivated protein kinase-related pathways are regulated and regulate Jun N-terminal kinase (JNK) expression, which has a pivotal role in obesity and insulin resistance [52]. Phosphatidylcholine, another component of the RA preparation, protects against oxidative stressmediated liver damage [53,54]. It is unlikely that the treatment effects are related to the vitamin E component, which is much lower (60 IU/ day) than doses with documented efficacy [4].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the intra-hepatic detection of lipid peroxidation products is prevalent in patients with NASH and correlates with necro-inflammation (11)(12)(13). Several lines of evidence in ALD indicate the involvement of immunological mechanisms in fuelling hepatic inflammation during the progression of the disease (27).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, antioxidant supplementation reduces liver injury in experimental rodent models of NASH (9,10). The relevance of these observations in humans is supported by several studies showing increased liver and serum content of oxidative stress markers, such as lipid peroxidation end-products, 8-hydroxy-2-deoxyguanosine (8-OHG), and nitrotyrosine in adult patients with NAFLD/ NASH (11)(12)(13). Moreover, microarray analysis of liver biopsies from patients with NASH demonstrated lower mRNA expression of different antioxidant enzymes (14).…”
Section: Introductionmentioning
confidence: 94%
“…The droplet serves as a means of safely storing fatty acids as triglyceride or exporting them through lipid transfer from the droplet to nascent very-low-density lipoproteins. Fat droplets are also targets for key regulatory hormones, including insulin, glucagon and epinephrine, through activity of fat droplet-associated surface perilipin/ADRP/TIP47 (PAT) proteins, which regulate lipase activity on the neutral lipid within the droplet [38][39][40]. Oxidative injury to the phospholipid monolayer around the droplets, altered expression of PAT in NASH and the interaction of droplets with cytoskeletal elements suggests that dysfunction of these organelles may be central to NASH pathogenesis [41][42][43][44][45][46].…”
Section: Fat Dropletsmentioning
confidence: 99%